1991
DOI: 10.1055/s-2007-1010596
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Endoscopic Retrograde Cholecystoendoprosthesis (ERCCE) for Cholecystitis

Abstract: Fourteen patients with cholecystitis were treated by endoscopic placement of an endoprosthesis into the cystic duct. In these patients the administration of antibiotics had failed to change the clinical picture of cholecystitis. Clinical and ultrasonographic findings before and two months after stenting were compared. There was an improvement in abdominal pain in 9 out of 14 cases (64%); fever, present in 5 patients, disappeared in all. No clinical complications were observed. Sonographic findings in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 0 publications
2
51
1
Order By: Relevance
“…Several investigators have reported that ETGBD is effective and safe for patients with acute cholecystitis (6)(7)(8)17) and that EGBS is one of the promising alternative treatment options (9)(10)(11)(12)(13)(14)(15)(16)(17). In patients with concomitant unresectable cancer, it is important to control infectious diseases, including acute cholecystitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators have reported that ETGBD is effective and safe for patients with acute cholecystitis (6)(7)(8)17) and that EGBS is one of the promising alternative treatment options (9)(10)(11)(12)(13)(14)(15)(16)(17). In patients with concomitant unresectable cancer, it is important to control infectious diseases, including acute cholecystitis.…”
Section: Discussionmentioning
confidence: 99%
“…Cholecystectomy is generally a safe procedure, but the surgical risk is high in patients with severe medical or surgical comorbidities (3). In such high-risk patients, percutaneous der stenting (EGBS) is a promising alternative treatment option for critically ill patients with symptomatic acute cholecystitis (10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24] Gallbladder stents have been used to treat acute cholecystitis, 22,24 biliary pain, 24 and subacute and recurrent cholecystitis. 23 Kalloo et al 24 reported excellent results with follow-up as long as 17 months in patients with similar advanced liver disease. Even when luminal patency is not maintained, biliary stents prevent stone impaction in the biliary tree in patients with endoscopically unextractable common bile duct stones, and existing reports in other patients suggest that excellent results may be achieved for up to 5 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Scattered case reports have suggested that endoscopic gallbladder stenting in high-risk patients may be effective. [20][21][22][23][24] We previously reported our preliminary experience of gallbladder stenting with successful outcomes in three patients. 25 In this report, we describe our prospective investigation evaluating the efficacy of endoscopic stenting of the gallbladder for symptomatic gallbladder disease in patients with ESLD awaiting OLT.…”
Section: Copyright 1999 By the American Association For The Study Of mentioning
confidence: 99%
“…Stenting of the gallbladder was first described in the early 1990s [5,6]. In a small retrospective series of 23 patients over a 10-year period, our group evaluated its efficacy in cirrhotic patients with biliary colic awaiting liver transplantation [7].…”
mentioning
confidence: 99%